Spontaneous pattern formation as a route to droplet motion - Langley, K. (2012)
Two important areas of physics are spontaneous pattern formation and droplet motion on surfaces. These two areas can be brought together since the texture of a surface can influence its wetting properties. Therefore by controlling the factors that determine the length scales of the patterns during spontaneous pattern formation, it is possible to design surfaces with very specific wetting properties. This was used to create surfaces that could direct the motion of sessile water droplets.